2021
DOI: 10.3390/electronics10233013
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hybrid Intelligent Secure Cloud Internet of Things Based Disease Prediction and Diagnosis

Abstract: Nowadays, more people are affected by various diseases such as blood pressure, heart failure, etc. The early prediction of diseases tends to increase the survival of affected patients by allowing preventive action. A key element for this purpose is the digitalization of the healthcare system through the Internet of Things (IoT) and cloud computing. Nevertheless, there are major problems in the cloud with the IoT due to false predictions and errors in medical data, which results in taking a longer time to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Furthermore, many researchers have done several studies on disease prediction to recognize and predict them in their early stages. A novel hybrid ML model was proposed based on the IoT for detection in the initial phase of diseases with an accuracy of 100% and a precision of 99.50% [ 37 ]. In another work, researchers have proposed an approach to predict cardiovascular disease according to various features.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, many researchers have done several studies on disease prediction to recognize and predict them in their early stages. A novel hybrid ML model was proposed based on the IoT for detection in the initial phase of diseases with an accuracy of 100% and a precision of 99.50% [ 37 ]. In another work, researchers have proposed an approach to predict cardiovascular disease according to various features.…”
Section: Related Workmentioning
confidence: 99%
“…However, the EMOE-UA technique has resulted in effectual outcomes with the ET and DT of 0.108 and 0.121 s respectively. From the above mentioned results, it is confirmed that the EMOE-UA technique has resulted in maximum performance over the other methods [29][30][31].…”
Section: Optimal Key Generation Using Issoamentioning
confidence: 57%
“…The security policies include technical security and privacy protection. The platform was implemented on a cloud system certified by ISO/IEC 27,799 for medical data storage and CSAP for cloud security certification [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%